Special Exercises Using A Proposed Training Apprentice And Its Effect On Some Biomechanical Indicators and Achieving 110m Hurdles - Muhammed, Zaha; Rashid, Imtsar (Journal of Physical Education, 2019)
The problem of the research lies in noticing that the body’s center of gravity passes a great curve while crossing the bar making it very heavy thus increases the time of crossing and breaks the motor pathway before, above and after the hurdle. Thus the researchers designed special exercises using a proposed device for hurdles to wear during crossing the hurdles. This device gives an audio signal to the hurdler that his crossing is within the range of the device’s laser. The research aimed at identifying the effect of this device on center of gravity height above the hurdle and its effect on the biomechanical variables before, above and after the hurdle. The subject was (6) elite 110m youth hurdlers. The special exercises were applied for (8) weeks with (3) training sessions per week. The data was collected and treated using proper statistical operations to conclude that the exercises have significant effect. Finally the researchers recommended the necessity of making similar studies using this device on other distances and hurdles.